Integration of Pumping in Virtual Power Players management considering demand response - Boldt, Diogo (2021)
The increase of distributed generation in several countries around the world brought several challenges to planning and operation of the electric network. In situations of high penetration of non-storable resources generation, mainly wind power, demand response programs and pumping may be applied, in order to encourage the increase of consumption, to guarantee a better electric network management. The present paper presents a methodology focusing on demand response programs, distributed generation and pumping, which aims to be used by a Virtual Power Player, who is able to manage the available resources optimizing its costs. The main objective is to use pump to store water to reservoirs, so the reservoir owner would have enough power to boost for energy generation. The case study includes 2223 consumers and 47 distributed generators, which was implemented using a Portuguese power system real scenario, 9th March 2014.